Cocconeis carinata sp. nov. (Bacillariophyceae) and re-examination of Cocconeis orbicularis Frenguelli & H.A.Orlando and Cocconeis reticulata var. deceptionis Frenguelli & H.A.Orlando. Issue 3 (3rd July 2019) - Riaux-Gobin, Catherine; Guerrero, Jose Maria; Ector, Luc; Witkowski, Andrzej; Blanco, Saúl; Daniszewska-Kowalczyk, Genowefa
Abstract : A small and rare (low in abundance) Achnanthales that was first discovered in the Kerguelen Archipelago (Austral Ocean), was subsequently found in the Mascarenes and Scattered Islands (Indian Ocean), and more recently in Nuku Hiva (Marquesas, South Pacific). This marine benthic taxon, first incorrectly identified as Cocconeis reticulata var. deceptionis Frenguelli & H.A.Orlando, is here described as Cocconeis carinata sp. nov. due to its unique features. The scarcity and small size of this diatom render its description difficult under light microscopy, while scanning electron microscopy allows a more detailed description. Cocconeis carinata sp. nov., a sternum valve of which was probably illustrated from the Florida Keys by Montgomery (1978), is a ubiquitous epiphyte and epipsammic taxon. The new taxon has some similarities with Cocconeis nitens Edsbagge, a taxon that is here typified, but with some differences in the stria density on both valves. A re-examination of the historic slides from which C. reticulata var. deceptionis and C. orbicularis Frenguelli & H.A.Orlando were described, leads to the conclusion that the former is a heterotypic synonym of the latter and, due to its complex structure, that C. orbicularis should be transferred to a more suitable genus.